Write On, Women! Discovering Personal Skills through Feminist Pedagogy and Narratives - Ana Olga Rallón; Anna Carolina Peñaloza-Rallón (Asociación Colombiana de Profesores de Ingles, 2021)
In this pedagogical proposal, we utilized Feminist Pedagogy and narratives to reveal women's skills that they had silenced in their cover letters for employment. Five females' narratives were analyzed using aspects of the grounded theory method to answer the question: What do women's narratives reveal about their personal skills otherwise silenced in their cover letters? The results showed that women find strength in their spirituality, as well as demonstrating loyalty, flexibility, respectfulness, and resilience. All of the women wrote about their decision-making abilities, which included organization, responsibility, and problem-solving. Finally, the stories revealed that women's ability to make choices defined their freedom and their future.